A Statistical Determination Of The Optimal Velocity In Coal Mine Entries ? Introduction - J. M. Mutmansky (Society for Mining, Metallurgy & Exploration, 1984)
A number of previous publications have attempted to provide the practicing ventilation engineer with simple guidelines on the optimal velocity to be used in mine openings. Some of these velocities were meant to be used in metal mining operations and some were meant for coal mining. A careful review of these publications reveals that the optimal velocities were determined based upon assumptions that are not existent today. As a result, they are not suitable for use in a modern coal mine. This paper takes a new look at this problem and determines a statistical relationship for optimal velocity that can be applied under both current and future conditions. The analysis performed here is based upon the determination of the optimal velocity for coal mine entries under variations in power cost, mining cost differential, airway friction factor, time value of money, airway lifespan, and quantity of air carried. A total of 8400 different conditions were analyzed for optimal velocity using computer calculation of the capital and operating cost values. Using the individual values of the optimal velocity derived in the calculations, a linear regression equation was fitted to the data to relate the optimal velocity to the other six variables outlined above. This regression relationship allows the ventilation engineer to make an easy, rapid determination of the optimal velocity.